Association between platelet indices and missed abortion - Bıyık, İsmail and Aslan, Mehmet Musa and Keskin, Fatih (Journal of Surgery and Medicine, 2019)
Aim: The incidence of missed abortion is around 15% of clinically diagnosed pregnancies, and the etiology is uncertain. Limited studies in the literature report increased platelet indices such as mean platelet volume (MPV), platelet distribution width (PDW), plateletcrit (PCT). The number of cases in these studies is low and results are inconsistent. There is no study that investigates all platelet indices. This study has the largest series in the literature and investigates all platelet indices in missed abortion. Methods: In this retrospective case-control study, the complete blood count parameters of patients who were diagnosed with missed abortion were examined. Among 500 cases, 228 women with missed abortion constituted the study group, and 272 healthy pregnant women constituted the control group. Women who were 18–45 years of age and 6–14 weeks of gestational age were included. Results: In the missed abortion group, PDW value was higher (P=0.007), while platelet MPV and PCT values were lower (respectively P<0.001 and P=0.008) than the control group. Conclusion: Platelet indices parameters in missed abortion are inconsistent.